Determinanty zróżnicowania pieniężnych dochodów ludności Polski w układzie wojewódzkim w latach 1976-1984 - Rutkowski, Tadeusz (Wydział Prawa i Administracji UAM, 1988)
The article presents spatial differentiation of the level of personal income in Poland and main components of that income, i.e. income from work in a socialized sector and revenues from the sale of agricultural produce. The main purpose was to determine the factors causing territorial differentiation of the said types of income through applying certain statistical and econometric methods (factor analysis and descriptive econometric models). The following determinants of differentiation of personal income were distinguished: — the rate of employment in a socialized sector; — the structure of employees according to age, sectors of State economy, the level of education; — the use of the region's territory for production purposes; — the value of the sold agricultural produce. The statistical and econometric analysis of spatial differentiation of the level of income carried out in the article creates the conditions for analysing the whole process of shaping the income in regional arrangement and allows to point out to the causes of that differentiation, what constitutes the basis for realizing by the State the efficient socio-economic policy with respect to regions.
Determinants differentiating income of people in Poland in years 1976- -1984 in regional arrangement